Renewable Energy Development for Buildings. (December 2016) - Tan, Hongwei; Lei, Yong; Chen, Yibo
Abstract: At the background of urbanization in China, energy consumption of buildings has been ranked as the second largest sector among the industry, building and transportation. Consequently, the renewable energy adopted in buildings has been quickly developed since the Chinese policy, which shifts 60% of total photovoltaic applications to the building sector, was enhanced. This paper discusses suitability of renewable energy applied in buildings, including solar thermal energy (ST), photovoltaic (PV) and geothermal heat pump systems (GSHP), based on GIS database and operation data analysis. GIS-based tools are also developed for evaluating suitability of renewable energy applied in buildings.